The use of mixed-method, part-body pre-cooling procedures for team-sport athletes training in the heat - Duffield, R.; Steinbacher, G.; Fairchild, T. J. (The Journal of Strength and Conditioning Research, 2009)
The current study investigated the effects of a pre-cooling intervention on physiological and performance responses to team-sport training in the heat. Seven male lacrosse players performed a familiarization session and 2 randomized, counterbalanced sessions consisting of a 30-minute intermittent-sprint conditioning session. Prior to the sessions, players performed a 20-minute mixed-method, part-body cooling intervention (consisting of cooling vests, cold towels to the neck, and ice packs to the quadriceps) or no cooling intervention. Performance was determined from collection of 1 Hz global positioning system (GPS) data and analyzed for distance and speed. Prior to, during, and following the sessions, core temperature, heart rate, rating of perceived exertion (RPE), and thermal sensation scale (TSS) were measured; additionally, a venous blood sample was collected before and after each session for measurement of interleukin-6 (IL-6), insulin-like growth factor (IGF-1) and insulin-like growth factor-binding protein3 (IGF-BP3). Results indicated that a greater distance was covered during the pre-cooling condition (3.35 ± 0.20 vs. 3.11 ± 0.13 km; p = 0.05). Further, most of this improvement was evident from a greater distance covered during moderate intensities of 7 to 14 km/h (2.28 ± 0.18 vs. 2.00 ± 0.24 km; p = 0.05). Peak speeds and very-high-intensity efforts (20 km/h ±) were not different between conditions (p > 0.05). The increase in core temperature was blunted following cooling, with a lower core temperature throughout the cooling session (38.8 ± 0.3 vs. 39.3 ± 0.4°C; p < 0.05). However, there were no differences in heart rate, RPE, TSS, IL-6, IGF-1, or IGF-BP3 between conditions (p > 0.05). Accordingly, the use of a mixed-method, part-body cooling intervention prior to an intermittent-sprint training session in the heat can assist in reducing thermoregulatory load and improve aspects of training performance for team sports.